Diversity of necrophagous flies and microbiome profiling of Phumosia promittens as a rainforest health indicator - Ahmad Azani, Othman; Nuralifah Insyirah, Mohamed Zain; Zolkapli, Eshak; Mohammad Adam, Adman; Zulkiflee, Abd Latif; Aboshanab, Khaled M.; Azwandi, Ahmad (Springer Nature, 2026)
Necrophagous flies play a critical role in decomposition and serve as bioindicators of environmental health and pollution. Malaysia’s tropical rainforest ecosystems may host many necrophagous fly species, including unique blowflies and their associated bacteria. However, in many forest reserve areas, the diversity of these flies remains poorly studied. This study examines the diversity of necrophagous flies and their associated surface bacteria community, with a particular focus on Phumosia promittens (Walker in J Proc Linn Soc Lond Zool 4:90–96, 1859) in the Bangi Forest Reserve, Universiti Kebangsaan Malaysia. Sampling was conducted across three plots using baited traps, and collected flies were morphologically identified and processed under sterile conditions. Surface bacteria from P. promittens were isolated and analysed through metagenomic analysis targeting the 16S rRNA (V3–V4) amplicon sequencing gene to characterise their microbial communities comprehensively. Among 2,528 individuals collected, Chrysomya megacephala (Fabricius) was the most dominant species overall, while P. promittens was the most abundant among native forest species, suggesting their ecological adaptability and potential as a bioindicator of healthy rainforest. Shannon–Wiener and Simpson’s diversity of flies in the study location were 0.67 ± 0.11 and 0.29 ± 0.06, respectively. Meanwhile, the Shannon–Wiener and Simpson’s diversity of bacteria from P. promittens were 5.64 ± 0.70 and 0.96 ± 0.02, respectively. Bacterial microbiome analysis revealed the presence of core genera, including Wohlfahrtiimonas, Dysgonomonas, Vagococcus, and Ignatzschineria, which are implicated in both ecological symbiosis and public health concerns. These bacteria may contribute to nutrient cycling, such as heavy metals and antibiotics. Notably, several of these genera are emerging zoonotic pathogens with antimicrobial resistance, highlighting the dual role of necrophagous flies as ecosystem contributors and disease vectors. The findings underscore the importance of monitoring native fly species and their microbiota to assess the integrity of forest ecosystems and potential public health risks.